Left Ventricular Reverse Remodeling With Biventricular Versus Right Ventricular Pacing in Patients With Atrioventricular Block and Heart Failure in the BLOCK HF Trial. (May 2015) - St. John Sutton, Martin; Plappert, Ted; Adamson, Philip B.; Li, Pei; Christman, Shelly A.; Chung, Eugene S.; Curtis, Anne B.
<x xml:space="preserve">Abstract</x> Background— Biventricular pacing in heart failure (HF) improves survival, relieves symptoms, and attenuates left ventricular (LV) remodeling. However, little is known about biventricular pacing in HF patients with atrioventricular block because they are typically excluded from biventricular trials. Methods and Results— The Biventricular versus Right Ventricular Pacing in Heart Failure Patients with Atrioventricular Block (BLOCK HF) trial randomized patients with atrioventricular block, New York Heart Association symptom classes I to III HF, and LV ejection fraction ⩽50% to biventricular or right ventricular pacing. Doppler echocardiograms were obtained at randomization (after 30 to 60 days of right ventricular pacing postimplant) and every 6 months through 24 months. Data analysis comparing changes in 10 prespecified echo parameters over time was conducted using a Bayesian design. LV end systolic volume index was also evaluated as a predictor of mortality/morbidity. Of 691 randomized subjects, 624 had paired Doppler echocardiogram data for ≥1 analyses at 6, 12, 18, or 24 months. Biventricular pacing significantly reduced LV volume indices and intraventricular mechanical delay, and improved LV ejection fraction, consistent with LV reverse remodeling. These parameters showed little change with right ventricular pacing alone, indicating no systematic reverse remodeling with right ventricular pacing. LV end systolic volume index was predictive of mortality/morbidity; the estimated risk increased up to 1% for every 1 mL/m2 increase in LV end systolic volume index. Conclusions— LV end systolic volume index is a significant predictor of mortality/morbidity in this population. Cardiac structure and function are improved with biventricular pacing for patients with atrioventricular block and LV systolic dysfunction. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT00267098.